2022
DOI: 10.1080/21655979.2021.2023984
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA HAGLROS inhibits metastasis and promotes apoptosis in nephroblastoma cells by inhibition of autophagy

Abstract: Nephroblastoma, or Wilms tumor, is a primary renal malignant tumor that easily occurs in children. Previous studies have revealed the regulatory functions of LncRNA in nephroblastoma. LncRNA HAGLROS functions as a tumor promotor in various cancers including hepatocellular carcinoma, ovarian cancer and colorectal cancer. In this study, the HAGLROS expression in nephroblastoma cells was assayed through qRT-PCR. Cell proliferation assessment employed CCK-8. Moreover, the migration and invasion of cells were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Circadian clock genes work together as a whole to regulate the body's life activities. And LncRNAs play pivotal roles in regulation of circadian clock genes, having different biological functions in various cancer types [ 18 , 19 ]. However, most studies conducted only on a single circadian clock gene, and fewer studies focus on the circadian clock genes as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circadian clock genes work together as a whole to regulate the body's life activities. And LncRNAs play pivotal roles in regulation of circadian clock genes, having different biological functions in various cancer types [ 18 , 19 ]. However, most studies conducted only on a single circadian clock gene, and fewer studies focus on the circadian clock genes as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that lncRNAs have vital roles in regulation of circadian clock genes. On the other side, LncRNAs play pivotal roles in regulation of circadian clock genes, having different biological functions in various cancer types [ 18 , 19 ]. Ming and colleagues showed that a lncRNA highly expressed in HCC can increase the expression of CLOCK to disrupt the circadian rhythm, resulting in the promotion of HCC [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we demonstrated for the first time that OSTM1-AS1 is highly expressed in WT tissues and cell lines. In addition, it has similar effects on WT cells as the lncRNAs MIAT [10], HAGLROS [21] and DGCR8 [22]. In this study, a series of in-vitro and in-vivo experiments demonstrated that OSTM1-AS1 knockdown considerably slowed the malignant development of WT cells.…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, we demonstrated for the first time that OSTM1-AS1 is highly expressed in WT tissues and cell lines. In addition, it has similar effects on WT cells as the lncRNAs MIAT [10], HAGLROS [21] and DGCR8 [22].…”
Section: Discussionmentioning
confidence: 99%
“…Например, lncRNA MIAT действует в качестве онкогена за счет регуляторного воздействия на DGCR8 (субъединица комплекса процессинга микроРНК) [60], lncRNA AC007406.1, AC005208.1, LINC01770, DLGAP1-AS2, AP002761.4, STPG3-AS1, AC129507.1, AC234772.2, LINC02447, AC009570.1, ZBTB20-AS1 и LINC01179 вовлечены в патогенез ОВ за счет влияния на ферроптоз [61], HOTAIR [62] и MEG3 [63] -на сигнальные пути Wnt/β-катенина. Нокдаун lncRNA HAGLROS ингибирует метастазы и способствует апоптозу клеток нефробластомы за счет ингибирования аутофагии [64]. Кроме того, lncRNA могут служить эффективными прогностическими биомаркерами ОВ.…”
Section: таблица 1 длинные некодирующие рнк (Lncrna) и их мишени влия...unclassified